Opportunities for improved clinical trial designs in acute respiratory distress syndrome. Issue 9 (September 2022) - Wick, Katherine D; Aggarwal, Neil R; Curley, Martha A Q; Fowler, Alpha A; Jaber, Samir; Kostrubiec, Maciej; Lassau, Nathalie; Laterre, Pierre François; Lebreton, Guillaume; Levitt, Joseph E; Mebazaa, Alexandre; Rubin, Eileen; et al.
Summary: The acute respiratory distress syndrome (ARDS) is a common critical illness syndrome with high morbidity and mortality. There are no proven pharmacological therapies for ARDS. The current definition of ARDS is based on shared clinical characteristics but does not capture the heterogeneity in clinical risk factors, imaging characteristics, physiology, timing of onset and trajectory, and biology of the syndrome. There is increasing interest within the ARDS clinical trialist community to design clinical trials that reduce heterogeneity in the trial population. This effort must be balanced with ongoing work to craft an inclusive, global definition of ARDS, with important implications for trial design. Ultimately, the two aims—to design trials that are applicable to the diverse global ARDS population while also advancing opportunities to identify targetable traits—should coexist. In this Personal View, we recommend two primary strategies to improve future ARDS trials: the development of new methods to target treatable traits in clinical trial populations, and improvements in the representativeness of ARDS trials, with the inclusion of global populations. We emphasise that these two strategies are complementary. We also discuss how a proposed expansion of the definition of ARDS could affect the future of clinical trials.